An Au nanocomposite based biosensor for determination of cholesterol. Issue 8 (25th March 2015) - Xu, Lin; Zhang, Mengdan; Hou, Yiting; Huang, Wei; Yao, Cheng; Wu, Qiong
Abstract : The present study aims to construct a biosensor to detect cholesterol by ChOx/HRP/Au/APTES/ITO. Abstract : The present study aims to construct a biosensor to detect cholesterol by ChOx/HRP/Au/APTES/ITO. We tested the electrochemical characterization of this electrochemical sensor electrode using a cyclic voltammetry (CV) technique. Meanwhile, the electron transfer properties of the electrodes after different surface modifications were characterized by electrochemical impedance spectroscopy (EIS). This study demonstrated AuNPs as efficient electron transfer mediators for enzymes based on electrochemical cholesterol biosensors. The calibration linear relationship range of cholesterol was 0.5–450 mg dL −1 with a sensitivity of 7.5 μA mg −1 dL −1 cm −2 . The excellent performances of the developed biosensor indicated that it can act as a promising candidate for the electrochemical detection of cholesterol.